Integrated Plastic Surgery Match: Trends in Research Productivity of Successful Candidates. Issue 1 (July 2020) - Ngaage, Ledibabari M.; Elegbede, Adekunle; McGlone, Katie L.; Knighton, Brooks J.; Cooney, Carisa M.; Cooney, Damon S.; Lifchez, Scott D.; Slezak, Sheri; Rasko, Yvonne M.
Abstract : Background: Plastic surgery continues to be one of the most competitive specialties in the residency match. Research productivity is a key component of the selection process. Nevertheless, potential applicants have a poor understanding of the strength of their research credentials in comparison to other applicants. Methods: The authors identified successful applicants from the 2012 to 2017 integrated plastic surgery residency application cycles. The authors performed a bibliometric analysis of these residents using Scopus, PubMed, and Google Scholar to identify published articles at the time of application. The authors then calculated the h -index of each applicant at the time of application. Results: The authors included 829 integrated residents. The median h -index was 0 (interquartile range, 0 to 3) and the median number of publications was 2 (interquartile range, 0 to 5) for all applicants. The proportion of applicants with at least one publication at the point of application increased significantly over time (60 percent in 2012 versus 76 percent in 2017; p = 0.0072). In addition, the number of publications per applicant increased over time (one in 2012 versus two in 2017; p = 0.0005), as did h -index (0 in 2012 versus 1 in 2017; p = 0.0015). Strikingly, the number and percentage of review articles among applicants increased significantly over this time frame (9 percent versus 14 percent; p = 0.0299). Conclusions: The increasing level of academic productivity among applicants may reflect the increasing competitiveness of the integrated plastic surgery residency application process. As the pressure to compete for a training position increases, students may seek faster-to-publish articles to gain an edge.